2020
DOI: 10.18632/aging.103941
|View full text |Cite
|
Sign up to set email alerts
|

CD45: a critical regulator in immune cells to predict severe and non-severe COVID-19 patients

Abstract: The ongoing outbreak of COVID-19 has been announced by the World Health Organization as a worldwide public health emergency. The aim of this study was to distinguish between severe and non-severe patients in early diagnosis. The results showed that the mortality of COVID-19 patients increased accompanied by age. Host factors CRP, IL-1β, hs-CRP, IL-8, and IL-6 levels in severe pneumonia patients were higher than in non-severe patients. CD3, CD8, and CD45 counts were decreased in COVID-19 patients. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 30 publications
9
24
0
Order By: Relevance
“…Higher antibody production has also been observed in severe COVID-19 patients 15 . Dynamic pattern of IL-6, C-reactive protein (CRP), fibrinogen, lactate dehydrogenase (LDH), platelet count and CD45 count may also be informative 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Higher antibody production has also been observed in severe COVID-19 patients 15 . Dynamic pattern of IL-6, C-reactive protein (CRP), fibrinogen, lactate dehydrogenase (LDH), platelet count and CD45 count may also be informative 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…PTPRC was earlier known as CD45 and it is one of the requisite factors for T-cell activation in atherosclerotic plaques [ 50 , 51 ]. Simultaneously, it has also been found as a potent marker for distinguishing severe and non-severe pneumonia in COVID-19 patients [ 52 ]. Thus it would be worthwhile to explore the roles of these hub genes in establishing the co-occurrence of atherosclerosis and COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…PTPRC was formerly known as CD45 which is an important antigen for activation of T-cells in atherosclerotic lesions [ 51 ]. Moreover, a recent study has revealed that CD45 could act as a potent marker for distinguishing severe and non-severe cases of COVID-19 [ 52 ]. Thus, CD45 which is found to be upregulated in Atherosclerosis datasets (GSE28829 and GSE100927) is equally important for both atherosclerosis and COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with severe COVID-19 pneumonia also present lower CD3, monocyte, CD8, and CD45 counts. CD45 is necessary for T cell activation [ 1 ]. In this case, alveolar exudate immunolabeling was positive for CD45, but negative for CD3.…”
Section: Discussionmentioning
confidence: 99%
“…Although SARS-CoV-2 has caused millions of infections and hundreds of thousands of deaths in the world, pathophysiological mechanisms of the disease are not yet elucidated. The analysis of clinical cases information is useful, helping to improve medical practice and to prevent complications and coinfections [ 1 ].…”
Section: Introductionmentioning
confidence: 99%